Relationship between happiness and emotional expressiveness among nursing student in University Malaysia Sabah - Mazlinda Musa; Segaran Ramodran; Floreta Yusop; Nur Shiela Abdul Majid; Nur Fatihah; Aqilah Roslin; Frettychriswella; Hanlin Hanis; Siti Fatimah Saat (Malaysian Journal of Medicine and Health Sciences, 2020)
Nursing is an emotionally stressful occupation where nurses themselves are at risk of internalizing negative emotions when caring for patients who are suffering, in pain, anguish, and facing death. Studies indicate an individual`s ability to emotionally express or vent these internalize negative emotions is associated with intrinsic happiness and well-being. Similarly, in the context of UMS, student nurses are at times exposed to overwhelming negative emotions during clinical postings and raise the question to what extent students use emotional expressiveness to vent such emotions. This study is to assess perceived happiness and emotional expressiveness and determine correlates of these attributes among student nurses in UMS. Methods: This study entails a cross-sectioned design involving 90 (N) participants selected through convenient stratified sampling from 1st year (n=30), 2nd year (n=30) and 3rd year (n=30) student nurses. Ethical clearance for this study was obtained from REC UMS and the respondent’s consent. Two validated instruments, the Intrinsic Happiness Index (IHI, with 10 Likert scaled items, α =0.78) and Emotional Expressiveness Scale (EES, 17 Likert scaled item α =0.82) were used in this study. Results: Among 90 nursing students in this study, 81%(n=72) scored high and 19% (n=18) scored low in the happiness index. On emotional expressiveness ratings, 68% scored high with 32% scoring low. Higher happiness index scores correlated positively with high emotional expressive scores. First year students had significantly higher perceived happiness score (p=0.02) and higher emotional expressiveness score (p=0.03) compared to 2nd or 3rd-year students. Conclusion: Finding in this study imply that although the majority of student had good emotional disposition, but a small percentage of students have lower perceived happiness and emotional expressiveness, which may affect long term psychological well-being. This paper will discuss some remedial strategies to address the issue.